Millennial Muslim Tourists’ Motivations and Characteristics at Marawa Beach Club: Motivasi dan Karakteristik Wisatawan Muslim Milenial di Marawa Beach Club - Mandalia, Siska; Fernanda, Aldi (Politeknik Pariwisata Makassar, Indonesia, 2024)
This research aimed to identify the dominant characteristics and motivations of millennial Muslim tourists visiting Marawa Beach Club Padang West Sumatra. Utilizing a quantitative research method, data was collected through the distribution of questionnaires. A simple random sampling technique was employed to select participants from the tourist population. The data were analyzed using quantitative descriptive analysis, with responses evaluated on a Likert scale of 1-5. Results from the questionnaires, completed by 100 respondents, highlighted distinct characteristics and motivations of millennial Muslim tourists compared to other visitor segments. This study reveals the unique appeal of Marawa Beach Club for this demographic. The findings provide valuable insights for tourism businesses, local authorities, and destination marketers aiming to cater to the specific preferences of millennial Muslim travelers. Additionally, this research lays a foundation for understanding evolving travel trends and informs strategies to create a more inclusive and enriching destination experience.